Pengaruh Literasi Keuangan, Financial Technology dan Inklusi Keuangan terhadap Kinerja Keuangan Pengusaha Muda. - Rahma Eka Putri; Goso Goso; Rahmad Solling Hamid; Imran Ukkas (Politeknik Ganesha Medan, 2022)
The development of entrepreneurship today needs to be improved through knowledge and experience, particularly in Indonesia as a developing country. This growth has also spawned several innovations such as literacy, financial technology, and financial inclusion to facilitate public access through financial services. This study aims to obtain data on the effect of financial literacy on financial performance, the impact of financial technology on financial performance, and the effect of financial inclusion on financial performance. The data used in this study are primary data obtained from questionnaires distributed to 179 MSMEs in North Luwu Regency. The hypothesis used is multiple regression with the help of SPSS. This study indicates that two variables have a significant effect, namely financial literacy on financial performance and financial technology on financial performance. And there is one variable that has no significant impact, namely financial inclusion on financial performance.